Helmet Use among Two Wheeler Female Riders - Khan, Rizwan; Krishnan, Nadia; Dhandapani, Manju; Dhandapani, Sivashanmugam (Indian Journal of Neurosurgery, 2019)
Introduction The frequency of traffic collisions in India is among the highest in the world with more than 135,000 traffic collision-related deaths occurring every year. The “Global Status Report on Road Safety” listed by the World Health Organization identified the major causes of injury as driving over the speed limit, driving under the influence, and not using helmets and seat belts. Women face unique challenges after traumatic brain injury, due to differential laws and their enforcement.Objectives To assess the use of helmet among female hospital workers (nurses, hospital attendants, sanitary attendants, and security guards) and their attitude toward helmet wearing.Methods Purposive sampling was done among female two-wheeler-riding hospital workers. A questionnaire was developed to study the use of helmet and an attitude Likert scale for assessing attitude toward wearing helmet. Data were collected, coded, and analyzed using SPSS software version 21.Results Of the total 89 women enrolled, 46.4% were mostly pillion riders, and 33% were mostly drivers. Only 19% were using helmet consistently, despite 93% owning it. Eighty-eight percent of the regular users were younger than 25 years, while 80% of the non-users were above 25 years. Even among regular drivers, 40% never wore helmet. Eighty-two percent of the non-users were merely casual despite knowing about its advantages.Conclusion Helmet use is very poor among women (both drivers and pillion riders), despite working in hospital environment and owning helmet. Stricter enforcement of helmet law is needed, as education and knowledge per-se may not instil helmet use.
Keywords: traumatic brain injury; helmet; pillion rider